Para-fiqh: Bridging Thematic Fiqh to Ushūl and Ushūl’s Response to Specialization of Fiqh - Siregar, Ahmad Sholihin (IAIN Samarinda, 2018)
The latest trend regarding the study of contemporary thematic Islamic jurisprudence (fiqh) is built upon a paradigm that fiqh, as a science developed in the Islamic tradition, is able to respond to every modern challenge. This paradigm seems to be incompatible with the study of the Islamic legal theory (UshÅ« al-fiqh) which is considered stagnant. However, the study of UshÅ« al-fiqh is, the initial gate to the discussion of legal reasoning which enables those who master it come up with theoretically correct rulings and hopefully responsive to the needs of the times. Discussing the thematic Islamic jurisprudence (fiqh) without going through the UshÅ« al-fiqh thinking framework may lead to a serious gap to the product of the thematic fiqh study. The thematic fiqh studies such as fiqh siyÄsah (Islamic jurisprudence on constitution), fiqh munÄkahat (Islamic jurisprudence on marriage), and Islamic jurisprudence on health issues are not infrequently distorted from the actual context. This article offers a way of dealing with the gaps. In this case, the terminology presented is para-fiqh. Para-fiqh is a term to bridge the trend between the thematic fiqh studies and the stagnancy of UshÅ« al-fiqh study which, in turn, give birth to the antithesis in the form of thematic UshÅ« al-fiqh. This article employs the conceptual-doctrinal approach which seeks to present the problems of various classical literatures of the Muslim scholars. By scrutinizing the concept para-fiqh, it is hoped that: first, this article presents a universal legal argument on some particular legal themes; second, it explains the principles of UshÅ« al-fiqh to understand the thematic fiqh products. The findings emphasize that the para-fiqh concept is important for enriching the intellectual tradition of Muslim communities, as well as being a bridge between the gaps created by the study of Islamic jurisprudence (fiqh) and the study of Islamic legal theory (UshÅ« al-fiqh).Keywords: para-fiqh; thematic ushÅ«l, thematic fiqh, UshÅ«l jinÄyat; UshÅ«l mu`Ämalat.